2006
DOI: 10.1038/sj.ki.5000097
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme (ACE) inhibition in type 2, diabetic patients – interaction with ACE insertion/deletion polymorphism

Abstract: Angiotensin-converting enzyme (ACE) insertion(I)/deletion (D) polymorphism may modify the effect of inhibition of the renin-angiotensin-aldosterone system (RAAS) on survival and cardiorenal outcomes in type 2, diabetes. A consecutive cohort of 2089 Chinese type 2 diabetic patients with mean (+/- standard deviation) age of 59.7 +/- 13.1 years were genotyped for this polymorphism by polymerase chain reaction method and were followed prospectively for a median period of 44.6 (interquartile range: 23.7, 57.5) mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 30 publications
6
45
1
Order By: Relevance
“…It has been demonstrated that T2DM patients with normoor micro-albuminuria carrying I allele had a better response to ACE inhibitor therapy compared to those patients with D allele. While, in T2DM with overt nephropathy and D allele there was a better response to angiotensin II receptor antagonists therapy compared to I allele (5,12,37,38). Similar comparable results were obtained in T1DM (39).…”
Section: Ace I/d Polymorphism and Response To Therapysupporting
confidence: 76%
“…It has been demonstrated that T2DM patients with normoor micro-albuminuria carrying I allele had a better response to ACE inhibitor therapy compared to those patients with D allele. While, in T2DM with overt nephropathy and D allele there was a better response to angiotensin II receptor antagonists therapy compared to I allele (5,12,37,38). Similar comparable results were obtained in T1DM (39).…”
Section: Ace I/d Polymorphism and Response To Therapysupporting
confidence: 76%
“…Consistent with data in type I diabetes, the study by So et al in 2089 Chinese patients with normoalbuminuria, microalbuminuria, or macroalbuminuria (44) found that over a median period of 44.6 mo, ACE inhibitor therapy decreased mortality, ESKD, or progression to estimated GFR Ͻ15 ml/min per 1.73 m 2 more effectively in II and ID than in DD carriers. This was the only study in type II diabetes with adequate power and follow-up.…”
Section: Ace Inhibitorssupporting
confidence: 70%
“…7,8 Furthermore, a reduced anti-albuminuric response to ACE inhibition has been demonstrated in type 1 diabetic patients with the D allele. 25 So et al 26 recently reported a large long-term observational study of a consecutive cohort of 2089 Chinese type 2 diabetic patients genotyped for the ACE/ID gene polymorphism. The study revealed that DD genotype enhanced the risk of a doubling of baseline serum creatinine concentration and ESRD.…”
Section: Discussionmentioning
confidence: 99%